Computing with logarithmic number system arithmetic: Implementation methods and performance benefits. (October 2020) - Parhami, Behrooz
Abstract: The logarithmic number system (LNS) has found appeal in digital arithmetic because it allows multiplication and division to be performed much faster and more accurately than with widely-used floating-point (FP) number formats. We present a comprehensive review and comparison of various techniques and architectures for performing arithmetic operations efficiently in LNS, using the sign/logarithm format, and focus on the European Logarithmic Microprocessor (ELM), a device built in the framework of a research project launched in 1999, as an important case study. Comparison of the arithmetic performance of ELM with that of a commercial superscalar pipelined FP processor of the same vintage and technology confirms that LNS has the potential for successful deployment in general-purpose systems. Besides paying due attention to LNS attributes beyond computational speed and accuracy, novel contributions of this survey include an exploration of the relationship of LNS with the emerging field of approximate computing and a discussion of the discrete logarithmic number system.